Environmental problems of the Zdovbytsia territorial community and ways to solve them - Siruk, I. M. (Man and Environment. Issues of Neoecology, 2025)
Purpose. To analyze the environmental problems of the Zdovbytsia United Territorial Community (Rivne region, Ukraine) and to propose practical solutions for their resolution in the context of sustainable development.Methods. Analytical approach, statistical, sociological, systematic analysis.Results. It was found that the most pressing environmental issues of the community include air pollution from vehicles and industrial enterprises, unauthorized landfills, insufficient modern waste disposal sites, deterioration of surface and groundwater quality, dust pollution from mineral extraction activities, and degradation of green spaces. A low level of environmental awareness among residents was identified, leading to weak support for environmental initiatives. Based on the analysis, the following solutions were proposed: implementation of separate collection and recycling systems for waste; establishment of official waste reception points; modernization of wastewater treatment facilities; enhancement of environmental monitoring of air and water resources; restoration of green zones; introduction of environmental education programs for students and adults; and encouragement of businesses to adopt environmentally friendly technologies.Conclusions. Effective resolution of the environmental problems in the Zdovbytsia community is possible through the combination of administrative, educational, and economic measures, as well as active cooperation between local authorities, the public, and the business sector. It is essential to ensure a systematic approach to environmental policy planning aimed at creating a safe, healthy, and comfortable living environment.